Evolutionary trends in the behaviour and morphology of the Anatidae - Johnsgard, Paul A (Wildfowl, 1962)
The major evolutionary trends most clearly evident in the Anatidae are as follows: 1) A trend from monomorphism to dimorphism in plumage, voice (including tracheal structure) and displays, in association with a trend from long pair bonds to temporary pair bonds. 2) A trend from generalized nesting and feeding adaptations to highly specialized ones, with associated specializations in diving adaptations and bill structure. 3) A trend from a single yearly body molt to two molts of the body plumage yearly, usually with an associated separation of nuptial and postnuptial (’eclipse’) plumages in males. 4) A trend towards the development of elaborate, often metallic-coloured, male plumage patterns and wing specula, associated with displays that exhibit these patterns.